49-(2x+16)=2(x+4)+x

Simple and best practice solution for 49-(2x+16)=2(x+4)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 49-(2x+16)=2(x+4)+x equation:


49-(2x+16)=2 (x+4)+x

We simplify the equation to the form, which is simple to understand
49-(2x+16)=2(x+4)+x

Remove unnecessary parentheses
49-2x-16=2*(x+4)+x

Reorder the terms in parentheses
49-2x-16=+(+2x+8)+x

Remove unnecessary parentheses
+49-2x-16=+2x+8+x

We move all terms containing x to the left and all other terms to the right.
-2x-2x-1x=+8-49+16

We simplify left and right side of the equation.
-5x=-25

We divide both sides of the equation by -5 to get x.
x=5

See similar equations:

| (5y/7)-15=5y+30 | | (5x+4)-(8x-6)= | | -4x^2+9x-1=0 | | 5k-(3k-5)= | | 7.3x=58.4 | | 5y^2-2y^3-7y^2+5y^3= | | 5(z-4)+7z-2= | | Y-2x=-1 | | 2x^2-12=5x | | 159-(7x+6)=7(x+9)+ | | 5w^2+3=-8w | | 2(3m+4)-3(m-5)= | | 8-(2x-6)=1-3x | | 3.7x=74.0 | | 4u^2-11u=3 | | x^2-12x-22.5=0 | | 2x^2-11x-63=0 | | 2(4z+7)-4(2-5)= | | 8x=-11y-16 | | 7*12+5= | | 124-(6x+16)=6(x+5)+x | | 3(3y-1)=6y | | 6p^2=-23p-15 | | 3(-4)(-6)= | | 6.4x-2.3x=73.8 | | 3(3r+5)-2(r+4)= | | -10n+16=-6n-12 | | 5.5x=55.0 | | 5(x+3)--7= | | 5x-4y=-26 | | x=3y-14 | | 5y=4(y+6) |

Equations solver categories